Effect of concrete strength and thickness of flat slab on preventing of progressive collapse caused by elimination of an internal column - Atefeh Soleymani (Iranian Society of Structrual Engineering (ISSE), 2019)
Designing structures against progressive collapse is an important part of the building design. However, some guidelines such as GSA and UFC holds implications for reducing the risk of progressive collapse of structures, but because the nature of the loads or events that cause damage are not well defined and the performance of building components during progressive collapse is not well understood, It is difficult to predict the trend of increasing damage. In this study, using the membrane action of the slabs, the effect of concrete strength and slab thickness on preventing the progressive failure of RC concrete slabs is investigated after the sudden removal of an internal column. Progressive collapse in the designed slabs was simulated by the sudden removal of an internal column and the slab capacity was calculated in the presence of compressive membrane force for different concrete strengths and slab thicknesses. Load carrying capacity for an enlarged span of the slab due to the sudden removal of the middle column has been investigated for various models. The results of this study showed that the membrane action of the slab, which is often not considered in design, can greatly prevent progressive failure of the slab and structure. By increasing the strength of the concrete and the thickness of the slab as well as the minimum recommendation of the regulation, the capacity of the slab can be considerably increased after the sudden removal of the middle column.